Backward nitrogen lasing actions induced by femtosecond laser filamentation: influence of duration of gain. (July 2015) - Xie, Hongqiang; Li, Guihua; Chu, Wei; Zeng, Bin; Yao, Jinping; Jing, Chenrui; Li, Ziting; Cheng, Ya
Abstract We experimentally investigate generation of backward 357 nm N2 laser in a gas mixture of N2/Ar using 800 nm femtosecond laser pulses, and examine the involved gain dynamics based on pump-probe measurements. Our findings show that a minimum duration of gain in the excited N2 molecules is required for generating intense backward nitrogen lasers, which is ∼0.8 ns under our experimental conditions. The results shed new light on the mechanism for generating intense backward lasers from nitrogen molecules, which are highly in demand for high sensitivity remote atmospheric sensing application.